Security system for stateless persons - Drakokhrust, Tetiana; Zhengrong, Luo (Актуальні проблеми правознавства, 2022)
Although there are many international treaties on the reduction or elimination of statelessness, national citizenship laws can also help. However, the fact is that the number of stateless people is still rising every year, and there is no effective legal regulation on them, and the living state is chaotic, and the lack of rights has not improved. This paper intends to clarify the urgency and importance of stateless people through the status quo and suggestions of the security system of stateless people, so as to lay the foundation for how to regulate stateless people, and how to solve the lack of rights and difficult life of stateless people, and provide a meager opinion for the solution of international human rights. The full text is mainly divided into individual and individual parts. The first part is the basic requirements of the legal regulation of stateless people; the second part is the improvement of stateless people. Finally, I conclude my conclusions and wishes for the problem of stateless people.